2020
DOI: 10.1038/s41593-020-0615-9
|View full text |Cite
|
Sign up to set email alerts
|

Four core properties of the human brain valuation system demonstrated in intracranial signals

Abstract: HAL is a multidisciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
116
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 90 publications
(150 citation statements)
references
References 52 publications
31
116
2
1
Order By: Relevance
“…Besides, HERs modulated value encoding in a multiplicative manner. Our results thus differ from a previously reported vmPFC baseline-shift additive effect in pleasantness ratings (Abitbol et al, 2015;Lopez-Persem et al, 2020). Altogether, our results indicate that part of the unspecified 'neural noise' driving fluctuations in choice consistency (Padoa-Schioppa, 2013;Kurtz-David et al, 2019;Webb et al, 2019) comes from the interaction between interoceptive self-related processes, indexed by neural monitoring of cardiac signals, and the neural encoding of subjective value.…”
Section: Discussioncontrasting
confidence: 99%
“…Besides, HERs modulated value encoding in a multiplicative manner. Our results thus differ from a previously reported vmPFC baseline-shift additive effect in pleasantness ratings (Abitbol et al, 2015;Lopez-Persem et al, 2020). Altogether, our results indicate that part of the unspecified 'neural noise' driving fluctuations in choice consistency (Padoa-Schioppa, 2013;Kurtz-David et al, 2019;Webb et al, 2019) comes from the interaction between interoceptive self-related processes, indexed by neural monitoring of cardiac signals, and the neural encoding of subjective value.…”
Section: Discussioncontrasting
confidence: 99%
“…Yet when the different frequency bands were put in competition for predicting PE across trials, low-frequency activity proved to be redundant, with respect to the information already contained in BGA. This result is in line with our analysis of subjective valuation for decision making (Lopez-Persem et al, 2020): all the information available in neural activity could be found in BGA, even if activity in lower-frequency bands also showed significant value signals.…”
Section: Specification Of Pe Signalssupporting
confidence: 90%
“…Indeed, manipulation of dopaminergic transmission was found to interfere with reward learning, specifically (Bodi et al, 2009;Frank, 2004;Rutledge et al, 2009), an effect that was captured by reward sensitivity in a computational model of learning in this task (Pessiglione et al 2006).The observation of reward PE signals in the lOFC was less expected, because it is generally not reported in meta-analyses of human fMRI studies and because several electrophysiology studies in animals suggested that, even if orbitofrontal cortex neurons respond to reward outcomes, they might not encode prediction errors (Roesch et al, 2010;Schultz, 2000). However, the similarity between lOFC and vmPFC reward PE signals is consistent with previous iEEG studies showing similar representation of subjective value and reward outcome in the two regions BGA (Lopez-Persem et al, 2020;Saez et al, 2018). Yet the lOFC and vmPFC reward PE signals may serve different functions, as was suggested by lesion studies in both human and non-human primates showing that the lOFC (but not the vmPFC) is critical for solving the credit assignment problem (Noonan et al, 2010(Noonan et al, , 2017.…”
Section: Dissociation Between Reward and Punishment Pesupporting
confidence: 71%
“…As such, our findings suggest that the contribution of OFC to decision making may be limited to situations that require model-based planning, and that choices based on direct experience may rely on value computations in other brain areas, such as the amygdala or striatum (Paton et al, 2006;Cox and Witten, 2019). This proposal is seemingly at odds with a large number of studies across different species that has shown neural correlates of both inferred and directly experienced value in OFC (Hare et al, 2009;Schoenbaum et al, 2009;Barron et al, 2013;Stalnaker et al, 2014;Howard et al, 2015;Padoa-Schioppa and Conen, 2017;Suzuki et al, 2017;Klein-Flugge et al, 2019;Lopez-Persem et al, 2020;Wang et al, 2020). Why would OFC represent value signals if they are not required for behavior?…”
Section: Discussionmentioning
confidence: 72%